MARKET PRODUCTION OF PLASTIC PIPES IN RUSSIA: DYNAMIC AND GROWTH PROSPECTS - MARINA VLADIMIROVNA Scherbina; SERGEY IGOREVICH Petuik (Мир новой экономики)
Investigation of the concentration of monopoly power in the market of the chemical industry is of great practical importance. Chemical Complex has a large share of GDP. Therefore, the definition of basic indicatorsand the competitive environment for the polyethylene segment of the chemical industry, namely plastic pipes is also important for the performance of public utility and for the oil industry. Forecasting demand in the global aspect is only possible with the analysis of the behavior of companies in the market. The article will be useful for analysts specializing in industry analysis, entrepreneurs who want to go out with plastics pipes in the world market.